Analysis Of Ion Levels Cr(Vi) In Groundwater Around The Textile Industry In Mojolaban With A Uv-Vis Spectrophotometer - Candra Kristiyani; Indah Tri Susilowati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
The textile industry has the potential to release liquid waste and contain heavy metals Cr. The toxicity of the most toxic Cr(VI) ions in liquid waste. The purpose of this study was to determine the quality of groundwater (borehole water) in terms of chemical parameters namely the levels of Cr(VI) ions. The type of research is observational analytic with the subject of 10 locations of groundwater around the textile industry in Village Mojolaban of Sukoharjo. The research data were obtained through questionnaire and testing the levels of Cr(VI) ions using UV-Vis Spectrophotometer The result showed the average of Cr(VI) ion levels obtained from each sample A to J are 1,4980 ppm; 1,6996 ppm; 1,2954 ppm; 1,5209 ppm; 1,4436 ppm; 1,4377 ppm; 1,3879 ppm; 1,3607 ppm; 1,3535 ppm; dan 1,3689 ppm. The average of Cr(VI) ion levels in groundwater studied exceeds the maximum levels of metals contamination allowed according to RI Permenkes No.32 in 2017. The average of Cr(VI) ion levels also exceeded the threshold of 0,05 ppm according to RI Permenkes No.416/Menkes/Per/IX/1990.